Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1177/1078345812456194
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges in Conducting HIV/AIDS Research in Correctional Settings

Abstract: To explore ethical challenges in the conduct and oversight of HIV/AIDS research in correctional settings, 92 researchers; IRB chairs, members, and prisoner representatives; research ethicists; and prison administrators were asked the question, "If you had to pick the single most important ethical challenge to HIV/AIDS research with incarcerated people, what would it be?" Data were analyzed with NVivo 8.0 software and revealed that key concerns were confidentiality and privacy; autonomy and informed consent; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 13 publications
(15 reference statements)
2
22
0
Order By: Relevance
“…Our research contributes empirical data to the national dialogue initiated by the IOM (2006) report on how to increase valuable research in correctional settings and confirms and expands on the qualitative findings reported by Eldridge et al (2012). Clearly, further research is needed to understand the situation before developing recommendations.…”
Section: Discussionsupporting
confidence: 55%
“…Our research contributes empirical data to the national dialogue initiated by the IOM (2006) report on how to increase valuable research in correctional settings and confirms and expands on the qualitative findings reported by Eldridge et al (2012). Clearly, further research is needed to understand the situation before developing recommendations.…”
Section: Discussionsupporting
confidence: 55%
“…Frequent, although not always “accepted,” practices such as drug use, same sex intercourse or commercial sex increase the risk of HIV acquisition or transmission among these confined individuals (53). However data relevant to these populations are limited (54). One global review regarding HIV in prisons showed that prevalences could be as high as 37.5% (55).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously highlighted the paucity of knowledge of federal regulations for protections of prisoners as research participants (Johnson et al, 2014) and ethical challenges related to research in correctional settings (Eldridge et al, 2012; Johnson et al, in press). The findings reported here expand our prior reports by identifying the specific areas of training desired.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the most significant of these ethical challenges, Eldridge, Robinson, Corey, Brems, and Johnson (2012) conducted key informant interviews with 92 HIV/AIDS researchers, ethicists, IRB members, IRB prisoner representatives, and prison administrators. These researchers found that confidentiality and privacy, autonomy and informed consent, and justice and access were the most commonly mentioned challenges.…”
Section: Introductionmentioning
confidence: 99%